Pengaruh Belanja Langsung dan Belanja Tidak Langsung terhadap Pertumbuhan Ekonomi Karisidenan Surakarta (Analisis Data Panel Dinamis) - Fernaldi Anggadha Ratno (Jurnal Bisnis dan Ekonomi, 2019)
This research is a quantitative descriptive research which is aimed to find out the effect of Direct and Indirect Expenditure towards the Economic Growth of Surakarta areas in 2009 – 2014. The technique of analysis used in this research is autoregressive distributed-lag dynamic model. This regression model includes not only the current but also the lagged values of the explanatory variable (Economic Growth). This regression model also includes one or more lagged values of the dependent variables (Direct and Indirect Expenditures) among its explanatory variable. The result of the analysis shows that Direct Expenditure gives more significant effect to the Economic Growth in Surakarta Areas, so does the Economic Growth of the past one year. Both Direct and Indirect Expenditure of the past one year give positive effects to the Economic Growth of Surakarta Areas in 2009 – 2014. Based on the analysis, it is recommended for the government to more thoroughly and carefully count the number of government expenditures to be allocated to economical activities which are able to contribute and positively affect the economic growth of a region or district. It is also recommended that government pays more attention to the allocation of Direct Expenditure which gives more significant value to the Economic Growth.